Miniaturized Microstrip Lowpass Filter with Ultra-Wide Stopband - Dou, Yan; Wang, Jianpeng; Cui, Haifei; Li, Jia-Lin (Applied Computational Electromagnetics Society Journal (ACES), 2021)
A new microstrip lowpass filter with compact size and ultra-wide stopband is presented. Using triangular patch resonators and butterfly resonator with four 45° radial “wing” patches, the introduced filter can successfully realize compact design and ultra-wide stopband. To further reduce the circuit size of the filter, the meander transmission lines are also adopted in the design. A demonstration filter with 3 dB cutoff frequency at 1.6 GHz has been designed, fabricated, and measured. Measured results show that the lowpass filter has an ultra-wide stopband bandwidth of 153.9 %, which is able to suppress the 11th harmonic response. Furthermore, it also has a small size of 14 ? 15 mm2, which corresponds to 0.114 ?g ? 0.122 ?g, where ?g is the guided wavelength at 1.6 GHz.